Soil fungal community and chemical properties are not directly affected by Bt cotton (Research, Society and Development, 2025)
Transgenic cotton has been cultivated in Brazil since 2005, including the plants which express the cry gene, derived from the entomopathogenic bacterium Bacillus thuringiensis (Bt). This technology has been considered efficient to control the target insect pests. However, little is known about whether these transgenic plants may impact the soil fungi and soil chemistry. This study aimed to evaluate the effects of genetically modified cotton resistant to insects on the soil fungal community and soil chemistry. The experiment was conducted in the agricultural area of Universidade Federal da Grande Dourados, Dourados Municipality, Mato Grosso do Sul State, Brazil. Two cotton (Gossypium hirsutum L.; Malvales: Malvaceae) cultivars were planted, one expressing a gene from Bt and the other without the foreign gene. Soil samples were collected monthly throughout the crop cycle. The amount of fungi in the soil was obtained by cultivation in Petri dishes, in triplicate, using Martin’s culture medium and soil serial dilutions. From the isolates, the morphospecies were identified by amplification and sequencing of the Internal Transcribed Spacer (ITS) region of rDNA. The number of fungal colony-forming units and species richness were not directly influenced by the type of cotton grown or by the different cotton growing stages. Similarly, cultivation of Bt cotton did not affect soil chemistry, but differences were observed regarding different sampling times. Overall, our research contributes to the current knowledge regarding agriculture in tropical areas, showing that there is no apparent evidence of the effect of Bt cotton on soil fungal communities and chemistry.